2021
DOI: 10.4330/wjc.v13.i9.438
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal violence: Serious sequelae for heart disease in women

Abstract: Experiencing various forms of violence in either childhood or adulthood has been associated with cardiovascular disease, both shortly after the event and during follow-up, particularly in women. The coronavirus disease 2019 pandemic has heightened the risk of domestic violence with serious sequelae for mental and cardiovascular health in women, possibly due to several contributing factors, ranging from lockdown, stay at home regulations, job losses, anxiety, and stress. Accordingly, it remains paramount to enf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…COVID-19 has increased the risk of DV with critical complications of mental and cardiovascular health in women. 60 Another study reported that among female survivors of DV, there was an augmented risk of cardiovascular disease, type 2 diabetes mellitus, and all-cause mortality. 61 Moreover, suicidality, injuries, psychological distress, unhealthy behaviors, sexual risk behaviors, and mental health outcomes have been reported as the consequences of intimate partner violence.…”
Section: Overview Of DV Against Women and Children During Covid-19mentioning
confidence: 99%
“…COVID-19 has increased the risk of DV with critical complications of mental and cardiovascular health in women. 60 Another study reported that among female survivors of DV, there was an augmented risk of cardiovascular disease, type 2 diabetes mellitus, and all-cause mortality. 61 Moreover, suicidality, injuries, psychological distress, unhealthy behaviors, sexual risk behaviors, and mental health outcomes have been reported as the consequences of intimate partner violence.…”
Section: Overview Of DV Against Women and Children During Covid-19mentioning
confidence: 99%
“…Many participants had one or more physician-diagnosed physical or mental health conditions. Being an IPV survivor or having PTSD is associated with adverse cardiovascular risk profiles (53)(54)(55), and it appears that many of the participants have factors that can elevate risks of developing future cardiovascular disease. Mainly, the participants engaged in healthy behaviors; most were physically active, engaging in sufficient physical activity to meet recommended targets for health (13), reported no or moderate alcohol intake, and only one reported smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, experts have warned that due to COVID-19 lockdown, cardiovascular health of IPV surviving women and the mental health of IPV surviving pregnant women might be severely affected. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, experts have warned that due to COVID-19 lockdown, cardiovascular health of IPV surviving women and the mental health of IPV surviving pregnant women might be severely affected. 13,14 Given the challenges of primary data collection during the pandemic period, shifts in policing priorities, and the absence of alternative sources of primary data, researchers have investigated the trend of IPV during pandemic using either helpline/emergency call logs or police reporting. 11,15 These data indicate significant increases in IPV-related calls during pandemic-led lockdown periods.…”
Section: Introductionmentioning
confidence: 99%